ANALISIS KONTRIBUSI PENGADILAN HUBUNGAN INDUSTRIAL DALAM PENYELESAIAN SENGKETA KETENAGAKERJAAN - -, Rizki; Simbolon, Julius Imanuel; Sianturi, Oki Berlin Roma Rezeki; Lumban Gaol, Glori Andika; Waruwu, Bryan Theofilus Gideon; Dewi, Nourma (jurnal.unprimdn.ac.id, 2023)
This research aims to analyze the Industrial Relations Court's (IRC) contribution in resolving labor disputes. Labor disputes often arise between workers and employers and have the potential to have a significant impact on industrial relations. The research method used is a literature study by collecting data from various sources such as scientific journals, reference books, and relevant policies and regulations. The data is then analyzed qualitatively to understand the role of IRC in resolving labor disputes. The analysis results show that IRC is essential to resolving labor disputes. IRC allows both parties to present their arguments fairly and objectively as an independent institution. Decisions made by IRC can create legal certainty for the parties involved. In addition, through the court process, IRC provides an opportunity for the broader community to obtain information about labor dispute cases and their legal interpretations. Therefore, efforts are needed to strengthen the capacity of IRC in order to provide more effective and efficient services. This research has important implications for developing industrial justice systems in resolving labor disputes. The findings of this study are expected to serve as a basis for government and relevant stakeholders to enhance the role of IRC and address existing challenges.